Interview of co-researcher from Bulgan aimag, January 5 and 11, 2022 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2022)
Includes interview of co-researcher from Bayankhongor aimag Jan 5, 2022
Keywords: Herders; Livestock; Travel; Vaccination; Democracy; Elections; Education; Festivals; Tsagaan Sar; Naadam; Pastoralist; Mongolia; Mobility; COVID-19 Pandemic